CALENDERIAL RITUAL SYAWALAN SEBAGAI MEDIASI â€œNGALAP BERKAHâ€ MASYARAKAT KALIWUNGU KENDAL - YANTO, HADI (Faculty of Humanities, Diponegoro University, 2013)
ABSTRACT Syawalan is a religious ceremony system in Javanese culture that has been a tradition to date carried out by traditional Muslim communities in Kaliwungu Kendal Regency in particular. This paper discusses the history, pattern, essence, meaning, and function of Syawalan as calenderial ritual tradition that has lasted decades. Syawalan as mediation